Prevalence of refractive error and other ocular morbidities among school going children aged 9-16 yrs in rural area of Mandya, Karnataka, India - BS, Vinay; BN, Shruthi (International Journal of Contemporary Pediatrics, 2016)
Background: Refractive errors, strabismus, vitamin A deficiency and infections of the eye are the various disorders, which affect school children. Most children initially may not be aware of the defective vision. Early detection of these problems and prompt treatment can prevent blindness in future. Therefore the objective of the study is to find out prevalence of refractive error and to identify the other ocular morbidities. Methods: A cross sectional study was carried out in school going children of age group 9-16 yrs in rural area of Mandya. Parental refractive error, close reading and TV watching were assessed in all children using questioners. All children were examined using Snellen’s chart. Results: In the survey of 362 children, majority of them were in 12-14 yrs of age group. The commonest cause of ocular morbidity in the present study was refractive errors which showed the prevalence of 8.28% followed by colour blindness, Squint and Vit A deficiency. The most common type of refractive error is myopia. As the age advances refractive error prevalence was also increased. Both boys and girls are almost equally affected. Conclusions: The results of the study strongly suggest that screening of school children for ocular problems should be done at regular intervals and it should be one of the prime components of School Health Program. School teachers should be oriented and trained to identify the common eye problems among school children’s so that the problems can be detected at the earliest and prevents co morbidities.